The Effect Of Five-Finger Hypnosis Therapy On Improving Adolescent Mental Health At State Senior High School 2 Gianyar - I Dewa Gede Candra Dharma; Ni Ketut Citrawati (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2026)
Adolescence is a critical developmental stage experienced by every individual, characterized by significant physical, biological, socio-emotional, and cognitive changes. Stress during adolescence commonly arises from the inability to adapt effectively to internal and external life demands, resulting in both psychological and physiological disturbances. Five-finger hypnosis therapy is a self-hypnosis intervention that induces deep relaxation, thereby helping to reduce mental tension and psychological burden. This study aimed to analyze the effect of five-finger hypnosis therapy on stress levels among adolescents. A quantitative quasi-experimental pretest-posttest design was employed, involving 40 tenth-grade high school students, with 20 participants assigned to the intervention group and 20 to the control group. Participants were recruited using a consecutive sampling technique. Stress levels were measured before and after the intervention using the Depression Anxiety Stress Scales (DASS) questionnaire. The intervention group received five-finger hypnosis therapy in four 10-minute sessions over one month, while the control group received no intervention. The findings showed that the control group remained predominantly at a moderate stress level before and after the study (60,0%). In contrast, the intervention group initially demonstrated predominantly severe stress (70,0%), which decreased to predominantly mild stress (90.0%) following the intervention. The Mann–Whitney test revealed a statistically significant difference in post-intervention stress levels between the intervention and control groups (p = 0,001; p < 0,05). These findings indicate that five-finger hypnosis therapy is effective in reducing stress levels among adolescents.